Solar FPC performance enrichment with Al2O3 / SiO2 nanofluids and hybrid nanofluid - T. Sathish; Jayant Giri; R. Saravanan; Mohd Sajid Ali; N. Muthukumaran (Case Studies in Thermal Engineering, 2024)
Sustainable energy harvesting plays a crucial role in advancing the goals outlined in the United Nations Sustainable Development Goals (SDGs). Solar flat plate collectors (FPC) are integral to sustainable energy harvesting, aligning closely with several Sustainable Development Goals (SDGs) particularly goals 7, 8, 9, 13 and 17. The heat transfer fluid is one of the most important inputs in the solar flat plate collector system. The improvement in the properties of heat transfer fluid significantly improves the collector efficiency. Though Nanofluid is one of the solutions, this investigation is motivated by the use of Al2O3 and SiO2 along Syltherm 800 in the form of nanofluids and hybrid nanofluid to improve the efficiency of FPC. The Syltherm 800 fluid (BF), Syltherm 800/Al2O3 nanofluid (ANF), Syltherm 800/SiO2 nanofluid (SNF), and Syltherm 800/Al2O3/SiO2 hybrid nanofluid (HNF) were tested and analysed to improve FPC performance. The results exemplified that using HNF improved the outlet temperature to the high of 126.9 °C, the average heat absorption of 4734.5 W, and the heat transfer coefficient (HTCO) of 166.3 W/m2K. The maximum average thermal efficiency and exergy efficiency of about 76.3%, and 49.8% respectively. Based on the experimental outcomes of the Syltherm 800/Al2O3/SiO2 hybrid nanofluid is recommended to improve the FPC thermal performances.